Closed Reduction of Developmental Dislocation of the Hip with Application of a Waterproof Cast: Master’s Surgical Technique - Christina Herrero; Michele N. Cerasani; Dylan Lowe; Wudbhav N. Sankar; Pablo Castañeda (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Developmental dysplasia of the hip (DDH) is the most common orthopaedic condition in infants. Approximately 1 in 10 infants are born with hip instability, 1 in 100 infants are treated for hip dysplasia, and 1 in 500 infants are born with completely dislocated hips. Due to the high prevalence of the pathology, there are clear algorithms for the diagnosis, treatment, and follow-up. An ultrasound should be performed if the infant exhibits any risk factors, either intrauterine or at birth. If it is positive for DDH, treatment is started, typically with a dynamic brace such as the Pavlik method. If bracing is unsuccessful or the infant presents at an age when it is deemed too late to start brace treatment, then closed reduction should be considered. Typically this is done under anesthesia holding the infant in the so-called human position and maintaining this for at least three months. One of the significant challenges of casting after a closed reduction is maintaining hygiene for the entire three months of treatment. This paper presents a detailed surgical technique guide to help physicians with closed reduction, casting with waterproof material, and advanced perioperative imaging to confirm reduction.